PERAN PENYULUHAN DALAM KEBERDAYAAN PETANI KARET POLA SWADAYA DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Yulida, Roza; ', Mhd. Daulai; ', Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rubber is one of the biggest living people of Riau. Most of the existing rubber plantations in Riau owned by non-farmers, who cultivated only on a small scale, unlike the case with a rubber plantation owned by the government or private parties. Not match results and widely owned by farmers, the government provides one solution to increase the productivity of farmers' production. The purpose of this study was to determine the roles of what is already run by agricultural extension in rubber farming in District XIII Koto Kampar Kampar District. Koto Kampar District XIII with an area of ​​smallholder rubber plantation in 2012 covering an area of ​​14.226 Ha chosen as the study site because it is a district with the largest non-pattern rubber plantation in Kampar regency. This research was conducted in the Village and Village Inscribed Stone Mountain Youngest District XIII Koto Kampar Kampar District. This method uses survey methods and data analysis performed by quantitative descriptive analysis using Likert scale. The results showed that the role of education has been less a role in the activities of non-pattern rubber farming in District XIII Koto Kampar Kampar District. Judging from education, dissemination, facilitation, consultation, supervision, monitoring and evaluation. The average value of the role of education is 2,73 (Self Serve), socialization is 2,62 (Self Serve), facilitated by 2.32 value (less a role), consultation is 2,26 (Less Acting), supervision of 2,38 (Less role) as well as monitoring and evaluation were 1,60 (Very Less role), so that the average overall role of education that 2,32 (Less Contribute).   Keywords: The role ofeducation, empowerment, independent rubberfarmers